Penataan Lembaga Kepresidenan melalui Undang-Undang tentang Lembaga Kepresidenan - Rizki Mubarok (Prosiding Seminar Hukum Aktual Fakultas Hukum Universitas Islam Indonesia, 2025)
This study examines the urgency of establishing a Presidential Institution Law within the Indonesian governmental system, which adopts a presidential system. The president's dual role as both head of state and head of government, along with extensive authority, necessitates clear regulations to define the functions, limitations, and accountability of the presidential institution. The absence of a Presidential Law to date has led to legal uncertainty and the potential for abuse of power. This research uses a normative approach through literature review and analysis of existing legislation. The findings of this study indicate that the lack of regulatory clarity regarding the presidential institution poses a threat to the principle of checks and balances and creates uncertainty in the distribution of authority between the president and other state institutions. Therefore, it is recommended to promptly establish a Presidential Law that clearly defines the powers and limitations of the president’s role, while also strengthening accountability and transparency in governance. Moreover, a more structured and explicit arrangement of the presidential institution will reinforce the principle of checks and balances in Indonesia’s governance, foster political stability, and uphold democracy.